Effect of addition of magnesium stearate on pollen shape hydroxyapatite drug carrier in dry powder inhaler formulations - Tan, Winnie Cai Ying. (2010)
Ternary mixtures composed of pollen-shaped hydroxyapatite (HA) carriers (38 – 75 µm), budesonide (Bd) drug (1 – 5 µm) and magnesium stearate (MgSt) fine particles (5 µm) were prepared at different mixing ratios. In addition, binary mixtures composed of HA carriers and Bd were also prepared as controls to investigate the effect of a ternary additive on the in vitro regional deposition and aerosolization properties of Bd. The effect of increasing Bd and MgSt concentrations in the formulations was also determined. The aerodynamic particle size distribution of Bd was measured using an eight-stage Anderson cascade impactor (ACI) after aerosolization at 60 L/min using a Rotahaler. All ternary mixtures produced a sufficiently high emitted dose (ED) of 90%. Blends containing a lower drug mixing ratio of 50:1 (HA:Bd, w/w) showed 3% improvement in fine particle fraction (FPF) of Bd compared to the control. In contrast, blends with a higher drug mixing ratio of 50:5 showed no improvement in FPF. The inhalation performance of HA carriers in ternary mixtures was also compared with conventional α-Lactose monohydrate (LA) carriers. All HA ternary blends achieved a higher ED of 90% as compared to 75% for LA ternary blends. However, HA ternary blends obtained a lower FPF of 10 – 18% in comparison to 24 – 34% of FPF for LA ternary blends.